2019
DOI: 10.1111/jpc.14402
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of red blood cell transfusion to neonatal morbidity and mortality

Abstract: Anaemia of prematurity will affect 90% of all very preterm infants, resulting in at least one red blood cell (RBC) transfusion. A significant proportion of preterm infants require multiple transfusions over the course of hospital admission. Growing evidence supports an association between transfusion exposure and adverse neonatal outcomes. In adults, transfusion‐associated sepsis, transfusion‐related acute lung injury and haemolytic reactions are the leading causes of transfusion‐related morbidity and mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 59 publications
1
45
0
Order By: Relevance
“…Several studies support a close association between transfusions and neonatal morbidity and mortality. [14][15][16][17][18][19][20] An evident result of top-up transfusions in preterm infants is that fetal haemoglobin, which should be physiologically high at this stage of life, is progressively replaced by adult haemoglobin. 21 In general, severely ill neonates are likely to receive a greater number of blood products, so that the causality between transfusions and negative outcomes is difficult to be ascertained in retrospective and prospective analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies support a close association between transfusions and neonatal morbidity and mortality. [14][15][16][17][18][19][20] An evident result of top-up transfusions in preterm infants is that fetal haemoglobin, which should be physiologically high at this stage of life, is progressively replaced by adult haemoglobin. 21 In general, severely ill neonates are likely to receive a greater number of blood products, so that the causality between transfusions and negative outcomes is difficult to be ascertained in retrospective and prospective analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The median HbF estimates are shown in the lower section of Table III. Overall, 465 HbF measurements were included in the analysis, corresponding to an average of 20 determinations per patient (IQR [16][17][18][19][20][21][22]. Cord-RBCs and adult-RBCs transfusions elicited significantly different HbF values (P < 0Á0001).…”
Section: Hbf Levels At 32 and 36 Weeks Of Post-menstrual Agementioning
confidence: 99%
“…Reports have found that approximately 90% of extremely low birth weight (ELBW) infants receive at least one RBC transfusion [3]. In general, RBC transfusion is able to improve anemia, increase tissue oxygenation, promote growth and reduce mortality [4,5]. However, considerable evidence suggests that RBC transfusion is related to several preterm disorders, including the development of ROP [5].…”
Section: Introductionmentioning
confidence: 99%
“…Long‐term neurodevelopmental and cardiac outcomes after IUT have been evaluated by Lindenburg et al in a review published in Prenatal Diagnosis . Blood transfusion may be an independent predictor of adverse neonatal outcomes and transfusion‐related immunomodulation and the effect of cofactors transfused with blood products are receiving research attention . Echocardiography has demonstrated reduced left ventricular mass in children followed up at a median age of 10 years following IUT for alloimmune anemia .…”
Section: Long Term Outcomes and Developmental Origins Of Health And Dmentioning
confidence: 99%